The Epidemiology of Cholera in Zanzibar: Implications for the Zanzibar Comprehensive Cholera Elimination Plan. (19th September 2018) - Bi, Qifang; Abdalla, Fadhil M; Masauni, Salma; Reyburn, Rita; Msambazi, Marko; Deglise, Carole; von Seidlein, Lorenz; Deen, Jacqueline; Jiddawi, Mohamed Saleh; Olson, David; Nemes, Iriya; Taib, Jamala Adam; et al.
Abstract: Background: Cholera poses a public health and economic threat to Zanzibar. Detailed epidemiologic analyses are needed to inform a multisectoral cholera elimination plan currently under development. Methods: We collated passive surveillance data from 1997 to 2017 and calculated the outbreak-specific and cumulative incidence of suspected cholera per shehia (neighborhood). We explored the variability in shehia-specific relative cholera risk and explored the predictive power of targeting intervention at shehias based on historical incidence. Using flexible regression models, we estimated cholera's seasonality and the relationship between rainfall and cholera transmission. Results: From 1997 and 2017, 11921 suspected cholera cases were reported across 87% of Zanzibar's shehias, representing an average incidence rate of 4.4 per 10000/year. The geographic distribution of cases across outbreaks was variable, although a number of high-burden areas were identified. Outbreaks were highly seasonal with 2 high-risk periods corresponding to the annual rainy seasons. Conclusions: Shehia-targeted interventions should be complemented with island-wide cholera prevention activities given the spatial variability in cholera risk from outbreak to outbreak. In-depth risk factor analyses should be conducted in the high-burden shehias. The seasonal nature of cholera provides annual windows of opportunity for cholera preparedness activities.